Skin signs of primary immunodeficiencies: how to find the genes to check. (1st February 2018) - Ettinger, M.; Schreml, J.; Wirsching, K.; Berneburg, M.; Schreml, S.
Summary: Primary immunodeficiencies (PIDs) are a heterogeneous group of rare diseases that result from defects in immune system development and/or function. The clinical manifestations of PIDs are highly variable, but most disorders involve at least an increased susceptibility to infection. Furthermore, cutaneous manifestations are very common in PIDs. As an easily accessible organ, the skin can be crucial for early diagnosis and treatment. This is relevant for preventing significant disease‐associated morbidity and mortality. We provide a table that enables the reader to find the possible diseases and corresponding gene defects based on the skin manifestations of the suspected PIDs. To our knowledge, this is the first review that allows the reader to find relevant PIDs and the respective gene defects through solitary or combined skin signs.